PENGARUH PROFESIONALISME, INDEPENDENSI, DAN PENGALAMAN AUDITOR PADA KUALITAS AUDIT BADAN PENGAWAS LEMBAGA PERKREDITAN DESA (LPD) - Dharma Putra, I Gede Adi; Wisadha, I Gede Suparta (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 8 No 2 (2013), 2013)
ABSTRACT A micro finance institution provides public financial services for micro to small business activities as well as low-income earners that are not able to access formal financial institutions. Village Credit Institution (called LPD) is a micro finance institution. It is supervised by a control body named Badan Pengawas, which acts as an internal auditor. The performance indicator of the control body would be the increase of audit quality and audit report, thus increase the function and credibility of the control body.  The aim of this research was to examine the effect of auditors’ professionalism, independence, and work experience on audit quality of control bodies of LPD in Denpasar city. A survey towards 33 LPD in Denpasar with 3 respondents each was conducted, providing 99 respondents in total. Samples are taken using purposive sampling method, including head of LPD, members of control body, and internal auditors. Data was collected using questionnaire and observation conducted in 2012. Data was then analyzed using multiple linear regressions. Hypotheses were tested using F-test and t-test. The results showed that simultaneously, auditor professionalism, independence, and experience affected audit quality of control body of LPD. Partially, each of independent variable affected audit quality of the control body of LPD in Denpasar city. Keywords: auditor experience, audit quality, independence, professionalism